The The Justice Dimensions in the Provision of Al-'Awl on Islamic Inheritance Law - Hafidz Taqiyuddin (Jurnal Hikmatuna, 2021)
This article explores one of the provisions in Islamic inheritance law, namely the provision of al-'awl. Al-'awl is a provision that makes the heirs’ share reduced from the legal portion that has been determined by al-nass. This research focuses on how the dimensions of justice are in al-'awl from Islamic theology and philosophy perspective. This research is a literature study using the Islamic legal philosophy approach. This approach is used in this research because the ushul fiqh approach is an approach that can reveal an object of research from the aspects of philosophy and theology. The study explores different fuqaha perspectives on al-'awl, so finally found that the al-'awl is a rule in the distribution of inheritance with dimensions of justice or benefit. The study’s result state that the solution to proportionally reduce the definite all heirs’ share is a solution that provides public benefits (maslaha) compared to reducing the exact share of some heirs. This research concludes that the provision in the distribution of inheritance that shows justice is a provision under the Allah SWT.’ destiny, In the form of death and family structure, and provisions that resolve problems, not harm family members left by the heir.